2002
DOI: 10.1071/wr02009
|View full text |Cite
|
Sign up to set email alerts
|

The index of relative importance: an alternative approach to reducing bias in descriptive studies of animal diets

Abstract: The Index of Relative Importance (IRI) is a composite measure that reduces bias in descriptions of animal dietary data. The two papers introducing the IRI in 1971 had been cited a total of 214 times by the end of 2001 and proposed as a standard methodology. However, 180 of these citations concerned the description of the diets of fish, indicating that the IRI is not well known outside fisheries biology. This illustrates how the interests of researchers in a narrow range of taxa may restrict the application of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
47
0
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 77 publications
(51 citation statements)
references
References 28 publications
3
47
0
1
Order By: Relevance
“…The index of relative importance has mostly been applied to fish diets, but some authors have suggested that it could be successfully applied to dietary studies in other animal groups (Hart et al 2002). The present study constitutes the first application of IRI to the study of bee diets.…”
Section: The Importance Of Iri To Assess Bee Dietsmentioning
confidence: 96%
See 4 more Smart Citations
“…The index of relative importance has mostly been applied to fish diets, but some authors have suggested that it could be successfully applied to dietary studies in other animal groups (Hart et al 2002). The present study constitutes the first application of IRI to the study of bee diets.…”
Section: The Importance Of Iri To Assess Bee Dietsmentioning
confidence: 96%
“…The advantage of IRI is that it combines number, frequency, and volume values avoiding the underestimation of food items (i.e., pollen types) with large volume but scarcely foraged, or reverse, which happens when these values are considered separately. Furthermore, food eaten by many individuals but in small numbers or small volumes will have a high frequency of occurrence, but may not be highly important in the diet (Pinkas et al 1971;Hart et al 2002).…”
Section: The Importance Of Iri To Assess Bee Dietsmentioning
confidence: 99%
See 3 more Smart Citations